Pallidal stimulation for pantothenate kinase-associated neurodegeneration dystonia. Issue 3 (4th March 2008) - Isaac, C; Wright, I; Bhattacharyya, D; Baxter, P; Rowe, J
Abstract : Pantothenate kinase-associated neurodegeneration is associated with generalised dystonia and cognitive deterioration. Limited evidence suggests that pallidal deep brain stimulation improves physical functioning. This is a report of the assessment and treatment of a severely affected patient in whom pallidal deep brain stimulation improved both physical and psychosocial functioning. Implications for treatment are briefly discussed.